Multi-Utility Solar Thermal Systems: Harnessing Parabolic Trough Concentrator Using SAM Software for Diverse Industrial and Residential Applications - Soufyane Naaim; Badr Ouhammou; Mohammed Aggour; Brahim Daouchi; El Mahdi El Mers; Miriam Mihi (Energies, 2024)
This study investigates the technical and economic feasibility of a 20 <semantics>MW</semantics> parabolic trough solar thermal power plant (PTSTPP) located in Kenitra, Morocco, characterized by an annual average direct normal irradiance (DNI) exceeding 5.3 <semantics>kWh/m2/day</semantics>. Utilizing System Advisor Model (SAM) 2012.12.02 software, the plant is designed with Therminol VP-1 as the heat transfer fluid (HTF) throughout the solar field, coupled with a dry cooling system to reduce water consumption. The proposed thermal energy storage (TES) system employs HITEC solar salt as the storage medium, allowing for six full load hours of thermal energy storage. With a solar multiple (SM) of 2, the simulated plant demonstrates the capability to generate an annual electricity output of 50.51 <semantics>GWh</semantics>. The economic viability of the plant is further assessed, revealing a Levelized Cost of Electricity (LCOE) of 0.1717 <semantics>$/kWh</semantics> and a capacity factor (CF) of 32%. This comprehensive analysis provides valuable insights into the performance, economic viability, and sustainability of a parabolic trough solar power plant in the specific climatic conditions of Kenitra, Morocco.